Safflor Yellow B Attenuates Ischemic Brain Injury via Downregulation of Long Noncoding AK046177 and Inhibition of MicroRNA-134 Expression in Rats. (4th June 2020) - Wang, Chaoyun; Wan, Hongzhi; Wang, Qiaoyun; Sun, Hongliu; Sun, Yeying; Wang, Kexin; Zhang, Chunxiang
Abstract : Stroke breaks the oxidative balance in the body and causes extra reactive oxygen species (ROS) generation, leading to oxidative stress damage. Long noncoding RNAs (lncRNAs) and microRNAs play pivotal roles in oxidative stress-mediated brain injury. Safflor yellow B (SYB) was able to effectively reduce ischemia-mediated brain damage by increasing antioxidant capacity and inhibiting cell apoptosis. In this study, we investigated the putative involvement of lncRNA AK046177 and microRNA-134 (miR-134) regulation in SYB against ischemia/reperfusion- (I/R-) induced neuronal injury. I/R and oxygen-glucose deprivation/reoxygenation (OGD/R) were established in vivo and in vitro . Cerebral infarct volume, neuronal apoptosis, and protein expression were detected. The effects of SYB on cell activity, cell respiration, nuclear factor erythroid 2-related factor 2 (Nrf2), antioxidant enzymes, and ROS were evaluated. I/R or OGD/R upregulated the expression of AK046177 and miR-134 and subsequently inhibited the activation and expression of CREB, which caused ROS generation and brain/cell injury. SYB attenuated the effects of AK046177, inhibited miR-134 expression, and promoted CREB activation, which in turn promoted Nrf2 expression, and then increased antioxidant capacities, improved cell respiration, and reduced apoptosis. We suggested that the antioxidant effects of SYB were driven by an AK046177/miR-134/CREB-dependent mechanism that inhibited this pathway, and that SYB has potential use in reducing or possibly preventing I/R-induced neuronal injury.